Effect of elevated temperature and carbon dioxide concentration of the mushroom growing environment on agronomic characteristics of tropical Agaricus bitorquis isolates - Pahil, V S; Smith, J F; Elliott, T J (Mushroom Research, 2015)
Please see the full paper